Sort by

- Relevance
- |Time

...the following. ∃x ∃y (((Px & Py) & ∀z (Pz > ((~

**Sxz**> (x = z)) & (~Oyz > (y = z))))) & Bxy) This says...2 Answers · Science & Mathematics · 09/05/2010

...0 Then D = (Sx2)(Sy2) - (Sxy)² a = [(

**Sxz**)(Sy2) - (Syz)(Sxy)]/D b = [(Syz)(Sx2...1 Answers · Science & Mathematics · 09/04/2013

The "constant" in the last equation is a 6th unknown. To solve, you need another equation or it's value. Oops... wait a minute... This might be helpful. Since all equations = 0, the left side of all equations equal each other. For...

1 Answers · Science & Mathematics · 27/04/2010